Use of High-Throughput Mass Spectrometry to Reduce False Positives in Protease uHTS Screens. (February 2015) - Adam, Gregory C.; Meng, Juncai; Rizzo, Joseph M.; Amoss, Adam; Lusen, Jeffrey W.; Patel, Amita; Riley, Daniel; Hunt, Rachel; Zuck, Paul; Johnson, Eric N.; Uebele, Victor N.; Hermes, Jeffrey D.
As a label-free technology, mass spectrometry (MS) enables assays to be generated that monitor the conversion of substrates with native sequences to products without the requirement for substrate modifications or indirect detection methods. Although traditional liquid chromatography (LC)–MS methods are relatively slow for a high-throughput screening (HTS) paradigm, with cycle times typically ≥60 s per sample, the Agilent RapidFire High-Throughput Mass Spectrometry (HTMS) System, with a cycle time of 5–7 s per sample, enables rapid analysis of compound numbers compatible with HTS. By monitoring changes in mass directly, HTMS assays can be used as a triaging tool by eliminating large numbers of false positives resulting from fluorescent compound interference or from compounds interacting with hydrophobic fluorescent dyes appended to substrates. Herein, HTMS assays were developed for multiple protease programs, including cysteine, serine, and aspartyl proteases, and applied as a confirmatory assay. The confirmation rate for each protease assay averaged <30%, independent of the primary assay technology used (i.e., luminescent, fluorescent, and time-resolved fluorescent technologies). Importantly, >99% of compounds designed to inhibit the enzymes were confirmed by the corresponding HTMS assay. Hence, HTMS is an effective tool for removing detection-based false positives from ultrahigh-throughput screening, resulting in hit lists enriched in true actives for downstream dose response titrations and hit-to-lead efforts.